Research Progress of All Organic Polymer Dielectrics for Energy Storage from the Classification of Organic Structures - Luo, Jiaming; Mao, Jiale; Sun, Wenjie; Wang, Shuang; Zhang, Lei; Tian, Liliang; Chen, Yu; Cheng, Yonghong (Macromolecular chemistry and physics, 2021)
Dielectric films are the foundation of power electronic equipment for energy storage in capacitors. However, typical dielectric films exhibit undesirable energy storage density and thermal stability, limiting its further application in the advanced field. For both pure polymers and composites‐based dielectrics, the macromolecular matrix greatly determines the performances. This paper summarizes the research progress of all‐organic polymer materials for the dielectric application from the perspective of molecular structure design. Systematic comparisons on properties, including dielectric constant and dielectric loss, glass transition temperature, and energy density are given, expecting to inspire researchers to devote further efforts in this area. An outlook for the future of all‐polymer dielectrics is also presented. This paper summarizes the research progress of all organic polymer materials for the dielectric application. Commercial and recently reported polymers for dielectric film used in capacitors are comprehensively reviewed. To highlight the structure‐property relationship, the polymers are classified based on their organic characteristics. Unlike composition, this review focuses on enhancing energy storage performance from molecular‐design perspective.